Чибориё тубатьёс: дуннеысь калыкъёслэн выжыкылъессы / суредаз В. Г. Мустаев - Баженова Галина Николаевна (Удмуртия, 2005)
Экземпляры: ф. 4 (20090401) / Инвентарный номер: 89501 / Цена: 40.00 / Авт.знак: Ч-58 / ГРНТИ: 17.71 / ББК: 84(0)